Management planning: Health challenges and practices (Research, Society and Development, 2022)
Management planning has been an important tool in the field of health, in order to promote the insertion of activities aimed at serving society, as well as in the quest to minimize the challenges in meeting all the demands of people who use health services. nowadays. Thus, the present research has the general objective of understanding the importance of management planning in minimizing challenges and contributing to health practice. In this conception, the methodology used corresponded to the integrative review method, in order to promote reflection on the state of the art, respecting the ideas and relationships of the authors. Through this, the results pointed to how much management planning presents the stages of policy definition; analyzes the health situation; builds operational modules as well as feasibility analyses, and enables a relationship to minimize existing challenges in the health area, also thinking about the goals to be achieved in the medium to long term. The authors also highlighted how much the strategies and actions included in management planning add value to the multidisciplinary team, seeking to direct which points should be improved and how to achieve the stipulated goals. The research concluded about the importance of planning in management to contribute to the minimization of challenges and practices in health, due to providing the necessary subsidy to professionals, working as a team with the bias of health management to understand which goals must be achieved and how professionals must create strategies to achieve your goals.